The historical development of islam and converts in Sabah, Malaysia: From the 14th century to the official designation of Islam as the state religion - Zaifuddin Md Rasip; Amir Hudhaifah Hamzah; Mohd Nur Hidayat Hasbollah Hajimin; Mohd Solleh Ab Razak; Sarip Adol; Syamsul Azizul Marinsah (Human Resource Management Academic Research Society (HRMARS), 2025)
This article examines the historical trajectory of Islam in Sabah, Malaysia from the 14th century to its official proclamation as the state religion in 1973, analyzing the key factors that facilitated the Islamization process alongside the challenges encountered. Employing a qualitative methodology, this study utilizes historical analysis and secondary sources, including manuscripts, colonial records, and prior scholarly works on the spread of Islam in Sabah. The findings reveal that Islam's dissemination was primarily driven by maritime trade, diplomatic engagements with the Sultanates of Brunei and Sulu, and the role of converts (mualaf) as intermediaries between Islam and indigenous communities. However, during the British colonial period, Islamic expansion faced significant impediments due to policies favoring Christianization, restrictions on Islamic missionary activities, and the expulsion of Muslim preachers. Following independence, the leadership of Tun Datu Mustapha and the establishment of the United Sabah Islamic Association (USIA) played a pivotal role in consolidating Islamic influence, resulting in an increase in the Muslim population from 38% in 1960 to 51% in 1980. The official designation of Islam as the state religion in 1973 further institutionalized Islamic governance through entities such as the Sabah Islamic Religious Council (MUIS) and the Syariah Court. This study concludes that structured da'wah strategies, effective political leadership, and institutional development were instrumental in ensuring the sustained presence and expansion of Islam in Sabah. By contributing to the historiography of Islam in Malaysia, this article also offers valuable insights into da'wah efforts and the socioreligious identity formation of Sabah’s Muslim community.